TABUNGAN PERUMAHAN RAKYAT (TAPERA) DAN PENERAPANNYA DI DKI JAKARTA - Putra, Henriko Ganesha; Fahmi, Erwin; Taruc, Kemal (Universitas Tarumanagara, 2019)
Occupancy is a basic need of every human being. As mandated by the 1945 Constitution, the State guarantees the fulfillment of citizens' needs for decent and affordable dwellings in the framework of developing Indonesian people who are wholly, self-conscious, independent and productive. The Public Housing Savings (Tapera) in accordance with Law of the Republic of Indonesia number 4 of 2016, is a long-term fund storage program that is used for housing finance, especially for Low-Income Communities (MBR). BAPERTARUM-PNS is an important lesson on how the goals of the housing savings are not utilized as retirement savings by most participants. The problem with this study is whether Tapera can be a solution for MBR in reaching funding for housing or repeating the failure of the BAPERTARUM-PNS program. Data collection from the Central Government, BP Tapera, and the Provincial Government of DKI Jakarta will be analyzed in the form of modeling of potential national and regional participation in and utilization of Tapera in DKI Jakarta Province. The results of the modeling analysis indicate a gap between Tapera's policies and people's expectations of a housing finance affordability solution for the MBR. AbstrakHunian merupakan kebutuhan dasar setiap manusia. Sebagaimana amanat UUD 1945, Negara menjamin pemenuhan kebutuhan warga negara atas tempat tinggal yang layak dan terjangkau dalam rangka membangun manusia Indonesia seutuhnya, berjati diri, mandiri, dan produktif. Tabungan Perumahan Rakyat (Tapera) sesuai Undang-Undang Republik Indonesia nomor 4 tahun 2016, merupakan program penyimpanan dana jangka panjang yang dimanfaatkan untuk pembiayaan perumahan, terutama bagi Masyarakat Berpenghasilan Rendah (MBR). BAPERTARUM-PNS menjadi pelajaran penting bagaimana ketidakberhasilan tujuan dari tabungan perumahan yang dimanfaatkan sebagai tabungan pensiun oleh sebagian besar peserta. Permasalahan dari studi ini adalah apakah Tapera dapat menjadi solusi bagi MBR dalam menjangkau pembiayaan untuk memperoleh hunian atau mengulangi ketidakberhasilan program BAPERTARUM-PNS. Pengumpulan data dari Pemerintah Pusat, BP Tapera, dan Pemerintah Provinsi DKI Jakarta akan dianalisis dalam bentuk Pemodelan potensi kepesertaan dan dana pemanfaatan Tapera secara nasional maupun regional di Provinsi DKI Jakarta. Hasil dari analisis pemodelan tersebut mengindikasikan adanya celah (gap) antara kebijakan Tapera dan harapan masyarakat akan hadirnya solusi keterjangkauan pembiayaan hunian bagi MBR.